Effect of Process Parameters on Microstructure and Mechanical Properties of Friction Stir Welded Cast Nickel Aluminum Bronze Alloy (C95800) - Selvaraju,Siva (2018)
In the present study, Friction Stir Welding (FSW) of Nickel Aluminum Bronze (NAB) alloy was carried out by varying the axial load, rotation speed and welding speed rate. Micro-structural analyses of these samples revealed the different grain sizes and shapes of the various zones. Hardness and tensile strength tests were carried out for the samples welded at different conditions such as axial load, welding speed and rotational speed. Grain refinement in the weld nugget zones was achieved for all welding conditions. The refined grains in weld nugget zone (WNZ) make a main contribution to the increase of mechanical properties of FSW welded NAB alloy. The microhardness of the stir zone and Thermo-Mechanically Affected Zone (TMAZ) was found to be higher than that of the base metal. Transverse tensile strength of weld joint was higher than that of the base metal. On the other hand, a lower or similar tensile strength value compared to the base metal was seen from other variable welding parameters. This was due to the tunnel defect in the welded nugget zone. ANOVA test result was used for finding out the contribution of the process parameter.